A Study on impact of foreign direct investment on manufacturing industries in Tanzania - MATONYA, Jordan Charles (KDI School, 2017)
Investment on Industries has been the centre core activity of many developing countries including Tanzania. Due to lack of capital, technology and managerial expertise Foreign Direct Investment has been opted as the best model to foster development of industrial sector. In recent years the government of Tanzania through privatization and building of trust to investors has started to witness much commitment on investment. This study intended to assess the effectiveness of Foreign Direct Investment (FDI) on promoting the development of manufacturing industries in Tanzania. The study employs the case study method where two manufacturing industries were involved. In addition, a bunch of secondary data from previous studies and government document was used to inform and get the picture of the study problem. Findings have shown that FDI had an influence and important role to Tanzania economy. Manufacturing industries in Tanzania today have a strong platform to play as compared to few years before privatization and those can be seen as fruits of FDI initiatives in the country. Lastly, this study recommends that, for real impact of FDI to be manifested to workers there is needs to enhance manufacturing sector objectives that will fit with current situation of investment in Tanzania.
Thesis(Master) --KDI School:Master of Development Policy,2017